Bleach-shade ceramic restorations for anterior teeth affected by fluorosis: a case report - T. B. Rakhymzhanov (Эндодонтия Today, 2025)
INTRODUCTION. Modern patients frequently strive for the brightest possible tooth shade, which often requires a full-mouth rehabilitation of both arches. However, in this clinical case, the 21-year-old patient’s teeth already exhibited a natural “bleach” shade, further complicated by fluorosis on the upper teeth. At the patient’s request, the objective was to adapt the upper anterior teeth to the already bright color of the remaining dentition. AIM. The aim of this work is to demonstrate the process of fabricating Bleach-shade ceramic restorations on six teeth (13–23) with minimal tooth preparation (0.5–0.7 mm). MATERIALS AND METHODS. Outlines the inclusion and exclusion criteria, the diagnostic steps, the selection of lithium disilicate ceramics, and the adhesive protocol (37% phosphoric acid etching of the enamel, HF etching of the internal surface, silanization, and resin cement). RESULTS. Observational results showed excellent esthetics and stable retention, without any inflammatory or painful symptoms. The uniqueness of this approach lies in the fact that Bleach restorations are typically performed only when both arches are comprehensively restored, yet here harmony was achieved without altering the lower teeth. CONCLUSION. The conclusions emphasize the potential of Bleach ceramics for patients seeking an “ultrawhite” smile, on the condition that the preparation and bonding technique are strictly followed.